Physicians’, pharmacists’, and nurses’ education of patients about antibiotic use and antimicrobial resistance in primary care settings: a qualitative systematic literature review - Balea, Lavinia Bianca; Gulestø, Ragnhild J. A.; Xu, Hongxuan; Glasdam, Stinne (Frontiers in Antibiotics, 2025)
BackgroundPatients’ adherence to antibiotic treatment and related prevention of AMR is significant. Understanding healthcare professionals’ strategies for advising and educating patients in primary care settings is crucial.AimFrom the perspectives of professionals and patients, to explore how physicians, pharmacists, and nurses educate patients about antibiotic use and antimicrobial resistance in primary care settings.MethodsA qualitative systematic literature review was conducted in MEDLINE, EMBASE, CINAHL Complete, Eric, SocINDEX, PsycInfo, Web of Science and Scopus. The study included 102 publications, followed PRISMA recommendations and was registered in PROSPERO (reg.no. CRD4202455761). The studies were screened and selected based on specific inclusion and exclusion criteria using Covidence. Quality appraisal followed the Critical Appraisal Skills Program (CASP) qualitative study checklist. Data were extracted, and the analysis consisted of a descriptive numerical summary analysis and a qualitative thematic analysis.ResultsThe analyzed studies spanned multiple countries and settings and included perspectives of primary care physicians, pharmacists, nurses and patients. Two main themes emerged: (1) Relationships between professionals and patients influenced educational strategies, showing that trust and rapport between healthcare professionals and patients played a crucial role in shaping educational strategies around antibiotic use; (2) The organizational structures challenged professionals in guiding and educating patients, highlighting how limited resources, time constraints, and system-level pressures hindered healthcare professionals’ ability to provide consistent and effective education. Often, structural challenges led to not educating the patients on the risks of antibiotic misuse and antimicrobial resistance. The use of delayed prescriptions emerged as a strategy for improved AMR stewardship and to meet patients’ expectations for antibiotic treatment, though it raised concerns about undermining professional responsibility and authority in ensuring appropriate antibiotic use.ConclusionHealthcare professionals’ role in educating patients about antibiotic use and AMR in primary care settings was complex, with different challenges faced by nurses, pharmacists and primary care physicians. These challenges extended beyond the clinical level, including relational, social and structural factors. Power dynamics, trust issues, and time pressures often hindered effective education on antibiotic use. Addressing gaps in education on antibiotic use and AMR requires acknowledging these multifaceted challenges, with future efforts focusing on better supporting healthcare professionals in this context.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD4202455761.